Non-Government Organization Practices on Peace Building Process - Munain Haron (Philippine Association of Institutions for Research, Inc., 2019)
Generally, this study aimed to determine the influence and contribution of the socio-demographic profile of the NGO officers and practices on the peace-building process. Specifically, it aimed to determine the socio-demographic profile of the NGO officers, the level of practices of NGO activities, the level of conduct of different initiatives on the peacebuilding process, and the effect of the socio-demographic profile and NGO practices on the peacebuilding process. 47 NGO officers who served as respondents of the study. Percentage and frequency were used to describe the socio-demographic profile of the officers. Mean was used to determine the level of practices of NGO and peace-building processes; multiple regression analysis was used to test the hypotheses of the study. It was found out that most of the NGO officers were under the age bracket of 26 - 30 years old male, Maguindanaon, married, primary and high school graduate in Arabic and English Education, had 11,000 - 20,000 monthly income and gave 600 - 1,500 weekly to support the operation of the organization. Findings further revealed that the NGO officers fully practiced relational dimension, peace-building agents, and communication and consultation.